An Indicator-Based Integrated Assessment of Ecosystem Change and Human-Well-Being: Selected Case Studies from Indonesia, China and Japan - Suneetha, M. S. (2012)
The paper highlights the findings of a study from selected ecosystems in Indonesia, China, and Japan. The study sought to trace changes to productive resources of ecosystems over a period of 50 years; and trace the dependence of well-being of local populations on the ecosystems for the same time period. Data was collected from land-use maps, records, and participatory rapid/rural appraisal (PRA) surveys in multistakeholder forums. To illustrate the changes, an indicator-based assessment framework was developed that integrates data from biophysical and socio-economic parameters. We observed that the approach (1) provides a better representation of the preferences of different stakeholders of ecosystem services, (2) fosters validation of data between the different stakeholders and (3) enables a communication and planning process among the stakeholders to sustainably utilize and manage their ecosystems. The use of spatial maps validates the relevance and utility of diachronic observations of communities and other stakeholders directly dependent on ecosystems. At the same time, they can be used to strengthen local planning processes for the development of services in the ecosystem. Such research thereby also acts as a catalyst to a social process of coordinated action to address local issues of global relevance.